Influência da pigmentação, técnica de união e envelhecimento acelerado sobre a resistência de união entre resina acrílica e silicone facial - Haddad, Marcela Filié [UNESP] (2013)
Maxillofacial prosthesis retained by implants use an acrylic framework to fit the attachment systems. However, the bond between acrylic resin and facial silicone is instable. Therefore, this study investigated the influence of nanoparticles pigments, adhesive system and accelerated aging on the bond strength between the acrylic resin and facial silicone. A total of 960 specimens made of selfpolymerized acrylic resin bar adhered to Silastic MDX 4-4210 facial silicone either colorless or pigmented with nanoparticles (oil tint and/or barium sulfate opacifier) were fabricated. The union between the two materials was performed in different ways: no treatment on the acrylic bar (N), mechanical retentions represented by scratches (R), application of prime for medical use (DC 1205 Prime - DC), primer for soft liner material (Sofreliner Primer MS - SF), and adhesive for medical use (Silastic Medical Adhesive Type A - A) alone or in combinations. The specimens were divided into 4 groups (n=240) according to the nanoparticle presence: Group 1: colorless; Group 2: oil tint; Group 3: opacifier; and Group 4: oil tint and opacifier. These groups were divided into 12 subgroups (n=20) according to the surface treatment used to bond the facial silicone to the acrylic resin: Subgroup I: N; Subgroup II: A; Subgroup III: DC; Subgroup IV: DC+A; Subgroup V: SF; Subgroup VI: SF+A; Subgroup VII: R; Subgroup VIII: R+A; Subgroup IX: R+DC; Subgroup X: R+DC+A; Subgroup XI: R+SF; Subgroup XII: R+SF+A. Half of the specimens of each subgroup (n=10) were subjected to bond strength test at the baseline period in a universal testing machine at a crosshead speed of 10 mm/min until failure. The other specimens were exposed to the accelerated...